Juvenile justice: the paradigm of formation and evolution - Bogatyreva, L.B.; Taitorina, B.A.; Abdukarimova, Z.T. (Bulletin of the Karaganda University “Law Series”, 2019)
The article discusses some issues of the formation and evolution of the institution of juvenile justice in foreign countries and in the Republic of Kazakhstan. As a result of the analysis of the historical patterns of the legal nature of international juvenile justice, it was concluded that the national models of juvenile justice of the states of the world community have some differences in the structure of their construction, as well as within their jurisdictional competence, but the basic and initial ideas of their purpose are the same, which is equally reflected in the national legislation of the states. The article analyzes the process of creating a modern juvenile justice system in the Republic of Kazakhstan. International standards for the rights of minors are implemented in the Constitution and legislation of the Republic of Kazakhstan. On the basis of the Concept for the Development of Juvenile Justice at the constitutional level in Kazakhstan, a number of measures have been taken. In the regions and cities of republican significance, 19 juvenile courts operate, the staff of which includes qualified inspectors-psychologists. Each regional prosecutor’s office has a special assistant who oversees the observance of the rights of minors; in some cities, the prosecutor’s bodies have specialized juvenile justice units. The local police service has a juvenile police unit. The system of advocacy is also specialized: specialized juvenile legal consultations operate. The principle of the best safeguarding of children's rights has been recognized as a priority in the activities of public authorities.